Does Side of Onset Influence the Pattern of Cerebral Atrophy in Parkinson’s Disease? - Santos, Maria C. A.; Campos, Lidiane S.; Guimarães, Rachel P.; Piccinin, Camila C.; Azevedo, Paula C.; Piovesana, Luiza G.; De Campos, Brunno Machado; Scarparo Amato-Filho, Augusto C.; Cendes, Fernando; D’Abreu, Anelyssa (Frontiers in Neurology, 2016)
Background Imaging studies have revealed widespread neurodegeneration in Parkinson’s disease (PD), but only a few considered the issue of asymmetrical clinical presentations. Objective To investigate if the side of onset influences the pattern of gray matter (GM) atrophy in PD. Methods Sixty patients (57.87 ± 10.27 years) diagnosed with idiopathic PD according to the U.K. Brain Bank criteria, 26 with right-sided disease onset (RDO) and 34 with left-sided disease onset (LDO), were compared to 80 healthy controls (HC) (57.1 ± 9.47 years). We acquired T1-weighted images on a 3 T scanner. Images were processed and analyzed with VBM8 (SPM8/Dartel) on Matlab R2012b platform. Statistic assessments included a two-sample test (family-wise error p < 0.05) with extent threshold of 20 voxels. Results Compared to HC, LDO patients had GM atrophy in the insula, putamen, anterior cingulate, frontotemporal cortex, and right caudate, while the RDO group showed atrophy at the anterior cingulate, insula, frontotemporal, and occipital cortex. Conclusion This study revealed widespread GM atrophy in PD, predominantly in the left hemisphere, regardless of the side of onset. Future investigations should also consider handedness and side of onset to better characterize cerebral involvement and its progression in PD.